(untitled) (Международный научный журнал «Инженер», 2026)
The article analyzes the objects of cultural purpose oriented to modern youth environment. The results of the study of transformation of volume-planning structure of modern youth spaces in the context of information society development are presented. The architectural and planning concept that can be used as a basis for the creation of a modern youth center is given.